Pengaruh Kesuburan Tanah terhadap Penyakit Blendok pada Pertanaman Jambu Mete - Ahmad Sulle (Jurnal Perlindungan Tanaman Indonesia, 2008)
Soil fertility can pressure rate attack of gummosis disease on cashew nut plantation in Muna Regency South-East Sulawesi. Blendok disease or gummosis have disseminated on some cashew plantation in Muna Regency, South-East Sulawesi. There was a correlation between soil fertilities and disease spreading. This assessment was intended to know the level attack and damage which were resulted from disease of gummosis at cashew crop. The assessment was conducted at Fongkaniwa Village of Muna Regency South-East of Sulawesi in 2004, using the rural cashew nut plantation in 30 ha area. The assessment area was divided into three blocks, i.e. high, moderate, and low level of soil fertility. Result of study indicated that attack intensity of gummosis disease on cashew nut are 19.49 %, 30.43 %, and 50.03 % on each levels of soil fertility, while Rate of Attack by the score value of 0.16, 1.14, and 1.77. Result of study indicated that improvement of soil fertility of cashew plantation are very important to pressure of attack and damage of gummosis disease.